2007
DOI: 10.1074/jbc.m606828200
|View full text |Cite
|
Sign up to set email alerts
|

ATP6 Homoplasmic Mutations Inhibit and Destabilize the Human F1F0-ATP Synthase without Preventing Enzyme Assembly and Oligomerization

Abstract: The molecular pathogenic mechanism of the human mitochondrial diseases neurogenic ataxia and retinitis pigmentosa and maternally inherited Leigh syndrome was determined in cultured human cells harboring homoplasmic T8993G/T8993C point mutations in the mitochondrial ATP6 gene, which encodes subunit 6 of the F 1 F 0 -ATP synthase. Immunoprecipitation and blue native electrophoresis showed that F 1 F 0 -ATP synthase assembles correctly in homoplasmic mutant mitochondria. The mutants exhibited a tendency to have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 38 publications
5
48
0
1
Order By: Relevance
“…A recent study of human (homoplasmic) NARP cells where the assembly of the ATP synthase has been thoroughly investigated led to the conclusion that this mutation has no significant effect on the assembly of the ATP synthase (45). In addition, the authors of this study provide evidence that the ATP synthase supramolecular structure is unaffected in NARP cells.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A recent study of human (homoplasmic) NARP cells where the assembly of the ATP synthase has been thoroughly investigated led to the conclusion that this mutation has no significant effect on the assembly of the ATP synthase (45). In addition, the authors of this study provide evidence that the ATP synthase supramolecular structure is unaffected in NARP cells.…”
Section: Discussionmentioning
confidence: 75%
“…In human NARP cells the assembly of the ATP synthase was reported in several studies to be unaffected by T8993G indicating that the impaired ATP production in these cells would be caused by a local disruption of the enzyme proton channel (19,45). However, others concluded that T8993G destabilizes the ATP synthase or slows down its assembly as indicated by an increased accumulation of ATP synthase subcomplexes in the mutant cells/tissues analyzed (13,21,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human ovarian cancer cell line OVCAR3 was grown in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum and 100 units/ml penicillin-streptomycin. Mitochondria and submitochondrial particles (SMPs) were isolated and prepared according to methods outlined previously (6,9,22). ATP synthesis activity by human mitochondria and mycobacterial membrane vesicles was measured as described previously (6, 9, 11).…”
mentioning
confidence: 99%
“…BNG and CNG also assess supercomplex formation. This type of analysis has been performed with muscle, platelets and fibroblasts from patients with suspected mitochondrial diseases [13][14][15][16][17][18]. For BNG, multisubunit OXPHOS enzymes bind a charged dye (Coomassie brilliant blue) which allows electrophoretic separation in the first dimension by the size of the complex.…”
Section: Data Formentioning
confidence: 99%